2017
DOI: 10.1021/acsnano.6b07159
|View full text |Cite
|
Sign up to set email alerts
|

Fermi Level Pinning at Electrical Metal Contacts of Monolayer Molybdenum Dichalcogenides

Abstract: Electrical metal contacts to two-dimensional (2D) semiconducting transition metal dichalcogenides (TMDCs) are found to be the key bottleneck to the realization of high device performance due to strong Fermi level pinning and high contact resistances (R). Until now, Fermi level pinning of monolayer TMDCs has been reported only theoretically, although that of bulk TMDCs has been reported experimentally. Here, we report the experimental study on Fermi level pinning of monolayer MoS and MoTe by interpreting the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

48
797
8
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 725 publications
(859 citation statements)
references
References 53 publications
48
797
8
6
Order By: Relevance
“…Recent experimental 20,61 and theoretical studies 60,62,63 have found a similar discrepancy. According to these studies, the Fermi level is partly pinned as a result of two interface effects: first, due to a metal work function modification resulting from a dipole formation at the interface, and second, by the introduction of gap states due to the weaker Mo–S bonding induced by interface metal–S interactions at the interface.…”
Section: Results and Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Recent experimental 20,61 and theoretical studies 60,62,63 have found a similar discrepancy. According to these studies, the Fermi level is partly pinned as a result of two interface effects: first, due to a metal work function modification resulting from a dipole formation at the interface, and second, by the introduction of gap states due to the weaker Mo–S bonding induced by interface metal–S interactions at the interface.…”
Section: Results and Discussionmentioning
confidence: 74%
“…According to these studies, the Fermi level is partly pinned as a result of two interface effects: first, due to a metal work function modification resulting from a dipole formation at the interface, and second, by the introduction of gap states due to the weaker Mo–S bonding induced by interface metal–S interactions at the interface. 62 To introduce Fermi level pinning into the Schottky–Mott rule, a pinning factor ( S ) and a charge neutrality level (ϕ CNL ) are added to eq 1(61,64,65) S is defined as S = d ϕ B / d ϕ M and can vary from 1 for an unpinned interface to 0 for a strongly pinned interface. b is the y -intercept of the ϕ B versus ϕ M graph, which is related to the ϕ CNL ashere, ϕ CNL is the energy at which the interface is electroneutral (see Figure 4a).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Such approaches may, for example, be relevant for achieving 2D metal film growth on 2D crystals, including graphene and Mo 2 S, and thereby synthesize low-resistivity electrical contacts on nanoelectronic devices [4,5,[7][8][9][10][11][12][13][14] or fabricate catalytic devices that exhibit enhanced turnover frequencies [6].…”
Section: Discussionmentioning
confidence: 99%
“…A notable example is the deposition of metal films on twodimensional (2D) crystals (e.g., graphene and MoS 2 ) [4][5][6] for which the tendency toward the formation of 3D agglomerates imposes technological obstacles for the use of 2D materials in a wide range of switching and, in some cases, catalytic devices [4][5][6][7][8][9][10][11][12][13][14]. Thus, understanding atomistic mechanisms that govern 3D island formation and shape evolution is a key step toward controlling film morphology and, by extension, the functionality of devices based on weakly interacting film/substrate materials systems.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, tungsten diselenide (WSe 2 ), which consists of one layer of W atoms sandwiched between two layers of Se atoms, has many excellent properties providing potential applications, including valley-based electronics 15,16 , spin-electronics, and optoelectronics 17,18 . More significantly, different from the unipolar n-type semiconductor MoS 2 with the presence of sulfur vacancy and the strong Fermi level pinning near the conduction band [19][20][21] , WSe 2 as an ambipolar semiconductor has been demonstrated as having Fermi level effectively shifting between the valence band and the conduction band under application of an external field [22][23][24] . Recently, the optical and hole dominant transport properties of exfoliated WSe 2 have been explored [24][25][26][27] .…”
Section: Introductionmentioning
confidence: 99%